Usability, acceptability, and feasibility of the Implementation of Infant Pain Practice Change (ImPaC) Resource. Issue 3 (30th May 2020) - Bueno, Mariana; Stevens, Bonnie; Rao, Megha; Riahi, Shirine; Lanese, Alexa; Li, Shelly‐Anne; ,
Abstract: The Implementation of Infant Pain Practice (ImPaC) Resource is an eHealth tool designed to support infant pain practice change and ultimately enhance pain outcomes. The aim of this study was to determine users' perspectives on usability, acceptability, and feasibility of the ImPaC Resource. A descriptive prospective mixed‐methods quality improvement study was conducted at a pediatric hospital in Canada. Individual "think aloud" interviews were conducted in a nonclinical environment (Phase A); "near live" testing was conducted while users interacted with the Resource in clinical setting (Phase B); individual "think‐aloud" interviews were conducted in a nonclinical environment (Phase C). Outcomes included usability (System Usability Scale—SUS), acceptability (Acceptability E‐Scale—AES), and feasibility. Interview transcripts were coded per a priori themes using deductive content analysis to create a structured categorization matrix. In Phase A, 10 clinicians interacted with the Resource in individual sessions. Median SUS score was 73.75 (range 52.5‐92.5). In Phase B, four clinicians implemented the Resource in the neonatal intensive care unit (NICU) over 4 months. Median SUS score was 85 (82.5‐92.5), and median AES score was 24 (21‐24). In Phase C, an enhanced prototype was produced, and the same users from Phase B navigated the Resource in individual sessions. Median SUS score was 88.75 (85‐95), and median AES score was 27.5 (25‐29). Users considered the Resource as feasible for implementation, easy to navigate, engaging, intuitive, comprehensive, and evidence‐based. Users highlighted the potential transferability of the Resource to other contexts and settings. The enhanced version of the ImPaC Resource was usable, acceptable, feasible, and met users' expectations and requirements. Results lead the way for evaluation of the Resource in a nationwide cluster randomized trial including 18 NICUs. This knowledge‐rich platform is expected to enhance infant pain practices and outcomes in diverse clinical settings.